2015
DOI: 10.1136/bmj.h846
|View full text |Cite
|
Sign up to set email alerts
|

Patient controlled analgesia with remifentanil versus epidural analgesia in labour: randomised multicentre equivalence trial

Abstract: Objective To determine women’s satisfaction with pain relief using patient controlled analgesia with remifentanil compared with epidural analgesia during labour. Design Multicentre randomised controlled equivalence trial. Setting 15 hospitals in the Netherlands. Participants Women with an intermediate to high obstetric risk with an intention to deliver vaginally. To exclude a clinically relevant difference in satisfaction with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 19 publications
7
119
0
6
Order By: Relevance
“…At the advice of reviewers and the journal's editors, we modified this to have a properly defined multiple outcome based on the requirement that pain not be inferior using the SSNB and that grip strength be superior. Following the recommendations of Freeman et al, 9 we used the area under the curve (AUC) from the NRS for the pain component and chose 10% of the total scale (1.1 units) as margin of noninferiority. Grip strength was assessed using the Modified Medical Research Council Scale for measuring hand muscle strength.…”
Section: Definition Of Study Outcomesmentioning
confidence: 99%
“…At the advice of reviewers and the journal's editors, we modified this to have a properly defined multiple outcome based on the requirement that pain not be inferior using the SSNB and that grip strength be superior. Following the recommendations of Freeman et al, 9 we used the area under the curve (AUC) from the NRS for the pain component and chose 10% of the total scale (1.1 units) as margin of noninferiority. Grip strength was assessed using the Modified Medical Research Council Scale for measuring hand muscle strength.…”
Section: Definition Of Study Outcomesmentioning
confidence: 99%
“…Freeman et al. recently confirmed that EA is superior as an analgesic during delivery; however, it is not clear whether better analgesia actually leads to increased satisfaction with the entire labor and delivery. Measurement of pain and satisfaction during labor is complex.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the traditional forms of labor analgesia such as pethidine (meperidine) and EA, RPCA is gaining popularity for the purpose of labor analgesia. This is noteworthy because studies comparing RPCA with EA found significantly higher pain scores for the RPCA group . Four studies comparing RPCA with EA showed that EA is a better analgesic, but maternal satisfaction scores were comparable for both, with no differences in type of delivery or neonatal outcome .…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations